2018
DOI: 10.1177/1464884918768494
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization in the Icelandic Press: An analysis of hard and soft news in major print and online media in Iceland in times of change

Abstract: This article examines the commercialization of content in print and online newspapers in Iceland over the past decade in the context of international trends. Market forces are said to be guiding the values and priorities of editorial decisions in news media in Western countries more than ever before. Traditional revenue models have been shattered and competition for audiences and advertising has intensified, not least because of technological changes. Research indicates that media in some countries are more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…As Bell [6] stated that the direct quoting making a journalist to have a grip on story by emphasizing with imparting information and wordings of source. results of research "Print media on coverage of political parties in Pakistan: Treatment of opinion pages of "Dawn" and "News" that "Dawn" is found in neutral tone as independent newspaper, while "The News" approach is subjective [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As Bell [6] stated that the direct quoting making a journalist to have a grip on story by emphasizing with imparting information and wordings of source. results of research "Print media on coverage of political parties in Pakistan: Treatment of opinion pages of "Dawn" and "News" that "Dawn" is found in neutral tone as independent newspaper, while "The News" approach is subjective [18].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis confirmed that the elite voice of people and other voices of organizations competed with newspapers as an influential medium. As per the research on "Print media on coverage of political parties in Pakistan: Treatment of opinion pages of "Dawn" and "The News" it is found from analysis from CDA and SFL that "Dawn" remained neutral in tone and language while the approach of "The News" is subjective [18]. The current study also has found "Dawn" reported the event with the neutral and liberal voice; while "The News" had shown moderate political alignment in current political situation by giving suggestions and experts" opinions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited research and data available on Iceland do suggest that the changes that have transformed the media landscape in the Western world in the last couple of decades (Lee-Wright et al 2012;Nielsen 2012;Fenton 2010;Currah 2009;Hardy 2008;Herkman 2008;Hallin & Mancini, 2004) have had similar effects in Iceland as elsewhere. Research indicates that commercialisation has increased considerably in the news (Jóhannsdóttir 2018;Guðmundsson 2013;Karlsson 2004) and that journalism as a profession is under increasing pressure (Guðmundsson & Kristinsson 2017;Guðmundsson 2012b). Like elsewhere traditional media, especially newspapers, are losing ground, and their business model is being undermined by the sweeping changes of digitisation.…”
Section: Stjórnmál and Stjórnsýslamentioning
confidence: 99%